Pirfenidone alleviates lipopolysaccharide-induced lung injury by accentuating BAP31 regulation of ER stress and mitochondrial injury. Issue 112 (August 2020) - Du, Yingzhen; Zhu, Pingjun; Wang, Xi; Mu, Mi; Li, Hongxia; Gao, Yanhong; Qin, Xuebing; Wang, Yan; Zhang, Zhijian; Qu, Geping; Xu, Guogang; Chang, Christopher; et al.
Abstract: Pirfenidone has been widely used in the treatment of idiopathic pulmonary fibrosis (IPF). However, the role of pirfenidone in LPS-induced acute lung injury (ALI) remains unclear. This study aims to investigate the protective effects of pirfenidone in ALI and to explore its underlying mechanism. Pirfenidone clearly reduces LPS-triggered ALI as indicated by significant pathological alterations, reduced oxidative stress and inflammatory responses in vivo . Furthermore, pirfenidone also blocks apoptosis of LPS-induced alveolar epithelial type II (ATII) cells through inhibition of endoplasmic reticulum (ER) stress and mitochondrial injury in vivo and in vitro . A lower expression level of BAP31, an ER transmembrane protein, was found to be associated with ALI followed LPS challenge. The reintroduction of BAP31 blunted LPS induced ER stress and mitochondrial damage and therefore alleviated ATII cell apoptosis, which correlated with pirfenidone treatment. Knockdown of BAP31 expression in pirfenidone treated ATII cells re-activated ER stress, mitochondrial damage and followed cellular apoptosis. In summary, this study confirms the beneficial effect of pirfenidone on ER stress and mitochondrial dysfunction mediated apoptosis via upregulation of BAP31. Our results demonstrated that pirfenidone may be considered as a potential agent for the treatment of ALI in the future. Highlights: ALI and its most severe form, ARDS are characterized by inflammation and diffuse alveolar damage. Pirfenidone reduces ALI by pathological alterations, reduced oxidative stress and inflammatory responses in vivo. Pirfenidone blocks LPS-induced apoptosis of ATII cells through inhibition of ER stress and mitochondrial injury. The reintroduction of BAP31 blunted LPS induced ER stress and mitochondrial damage and alleviated ATII cell apoptosis. Knockdown of BAP31 in pirfenidone treated ATII cells re-activated ER stress, mitochondrial damage and cellular apoptosis.